Neoadjuvant chemoimmunotherapy versus neoadjuvant chemoradiotherapy in patients with borderline resectable esophageal squamous cell carcinoma - Jun-Peng Lin; Feng-Nian Zhuang; Wei-Jie Chen; Zhou Lin; Yu-Jie Chen; Xiao-Feng Chen; Hui Lin; Hao He; Peiyuan Wang; Hang Zhou; Wen-Wei Wei; Peng-Qiang Gao; et al. (Journal of Translational Medicine)
Abstract Background The optimal treatment strategy for patients with borderline resectable (cT3br) esophageal squamous cell carcinoma (ESCC) remains unclear. Thus, the aim of this study was to compare the perioperative outcomes and prognoses between neoadjuvant chemotherapy combined with immunotherapy (NACI) and neoadjuvant chemoradiotherapy (NCRT) in cT3br ESCC patients. Methods In this retrospective cohort study, patients with cT3br ESCC who received either NACI or NCRT followed by surgery between January 2016 and December 2022 were identified. Propensity score matching (PSM) was used to minimize the influence of confounding factors. Survival curves were constructed and analyzed using Kaplan–Meier log-rank survival analysis. Results 97 patients with cT3br ESCC received NACI and 111 received NCRT. After PSM, the R0 resection rate (85.7% vs. 90.5%, P = 0.341) and pCR rate (19.0% vs. 26.2%, P = 0.269) were comparable between two groups, while the MPR rate in the NACI group was significantly lower than in the NCRT group (32.1% vs. 56.0%, P = 0.002). However, NCRT was associated with a greater risk of severe postoperative complications (21.4% vs. 6.0%, P = 0.004). The 3-year overall survival (69.4% vs. 55.7%, P = 0.242), disease-free survival (55.7% vs. 49.7%, P = 0.242), overall recurrence (32.1% vs. 29.8%, P = 0.739), and recurrence patterns were comparable between the NACI and NCRT groups. Conclusion NACI followed by surgery appears to be a safe and effective treatment strategy for patients with borderline resectable ESCC.